Diversity of Aerobic Bacilli Analysis Using Molecular and Culture-Based Approaches in Debagh Hot Spring. Issue 2 (7th February 2019) - Arab, Mounia; Bakour, Sofiane; Lalaoui, Rym; Aissaoui, Nadia; Nas, Fatima; Hoceini, Amina; Fournier, Pierre-Edouard; Klouche-Khelil, Nihel
Abstract: This study reports the first attempt to describe aerobic bacilli communities in Debagh hot spring, from which 41 aerobic, thermophile, and halotolerant bacilli were isolated and selected based on morphological, physiological, and biochemical tests. 16S rDNA sequence analysis revealed that the recovered isolates belonged to four bacterial genera dominated by the genus Bacillus represented with species B. mojavensis (16), B. licheniformis (11), B. subtilis (2), B. atrophaeus (1), B.amyloliquifaciens (1), and B .pimulus (1). The genus Aeribacillus represented by the species A. pallidus (3), the genus Geobacillus represented by the species G. toebii (2), and the genus Hydrogenophilus represented by the species H . hirschii (4). While, MALDI-TOF analysis determined that isolates belonged to the genus Bacillus that contained B. licheniformis (12), B. mojavensis (6), B. subtilis (2), B. atrophaeus (1), and B. pumilus (1). Furthermore, the isolates exhibited high hydrolytic activity to casein, lecithin, tween 80, olive oil, and starch with 53.65%, 83.33%, 70.73%, 92.68%, and 56.09%, respectively. Among these isolates, 26.82% were able to hydrolyze all the substrates tested.